Boosting Charge Transport in BiVO4 Photoanode for Solar Water Oxidation. Issue 8 (18th January 2022) - Lu, Yuan; Yang, Yilong; Fan, Xinyi; Li, Yiqun; Zhou, Dinghua; Cai, Bo; Wang, Luyang; Fan, Ke; Zhang, Kan
Abstract: The ability to regulate charge separation is pivotal for obtaining high efficiency of any photoelectrode used for solar fuel production. Vacancy engineering for metal oxide semiconductor photoelectrode is a major strategy but has faced a formidable challenge in bulk charge transport because of the elusive charge self‐trapping site. In this work, a new deep eutectic solvent to engineer bismuth vacancies (Bivac ) of BiVO4 photoanode is reported; the novel Bivac can remarkably increase the charge diffusion coefficient by 5.8 times (from 1.82 × 10 −7 to 1.06 × 10 −6 cm 2 s −1 ), which boosts the charge transport efficiency. Through further loading CoBi cocatalyst to enhance charge transfer efficiency, the photocurrent density of BiVO4 photoanode with optimal Bivac concentration reaches 4.5 mA cm −2 at 1.23 V vs reversible hydrogen electrode under AM 1.5 G illumination, which is higher than that of previously reported Ovac engineered BiVO4 photoanode where the BiVO4 photoanode is synthesized by a similar procedure. This work perfects a cation defect engineering that enables the potential capability to equate the charge transport properties in different types of semiconductor materials for solar fuel conversion. Abstract : The formation of hole polarons is the main cause of the slow migration of hole carriers to the surface for BiVO4 photoanode, which is localized at the BiO8 unit cell. A deep eutectic solvent that can leach Bi atoms from the BiVO4 crystal to selectively destroy the unit structure is reported. After losing Bi atoms from the BiVO4 crystal, the hole carriers will be in a more chainless state and can reach the surface with a faster migration speed to participate in the water oxidation.